Effect of Ratio of Residual Alveolar Bone to Graft Material in Contact With Fixture Surface on Marginal Bone Loss of Implants in Augmented Maxillary Sinuses: A 1-Year Retrospective Study. Issue 1 (February 2017) - Park, Chan-Ho; Lee, Dong-Won; Yun, Jeong-Ho; Moon, Ik-Sang
Abstract : Purpose: The purpose of this retrospective study was to evaluate the influences of height or area ratio of residual alveolar bone to graft material on marginal bone loss around implants in the augmented maxillary sinuses with delayed implant placement. Materials and Methods: In this study, 42 patients with Astra implants in sinuses that had been augmented with alloplasts and allografts or xenografts (alveolar bone height ⩽ 5 mm) were selected. Marginal bone level surrounding 1 implant per sinus was assessed by radiographic imaging at the time of final restoration delivery and 12 months after functional loading. To evaluate the marginal bone level alterations using clinical and radiographic data, Pearson's correlation analysis and Mann–Whitney test were performed. Results: Forty-six implants were included in this study. The residual bone/implant length ratio and the residual bone/implant area ratio were not associated with marginal bone loss at 1 year after functional loading ( P > 0.05). And, marginal bone loss did not differ significantly between 2 types of graft materials during the observation period ( P > 0.05). Conclusion: The residual bone/implant length ratio and residual bone/implant area ratio were not associated with marginal bone loss around implants placed in augmented sinuses during 1 year of functional loading.